CLASSICAL CHINESE PHILOSOPHY AND THE CONCEPT OF QI - Rošker, Jana S. (NEARCO - Revista Eletrônica de Antiguidade e Medievo, 2021)
The concept of qi belongs among the most difficult and complex notions in Chinese ideational history. The present article follows from recognizing that traditional translations of this concept are Eurocentric. The author substantiates the problematic role of these presumptive translations through critical analyses of their methodological approaches, which led to the traditional, falsified understanding of this concept. A new alternative and richer understanding of this concept is proposed, pointing to several different levels of meaning on which it can be understood. The author analyses and interprets the notion of qi including its various philosophical, physiological, psychological end ethical dimensions. The article shows that on the semantical level, qi derives from the etymological meaning of air and is in essence similar to the concept of field in physics, referring to the breath as the origin of the living world. From this perspective, the holistic nature of this notion of breath will be introduced, exposing the dynamic network through which it connects all existing beings in the universe, endowed with life.